EFFECT OF MORPHOLOGICAL CHARACTERISTICS OF PRECISION IN BASKETBALL - Nazim Myrtaj (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
Basketball in its structure is very complicated and complex activity in which kinesiology success depends on the influence of a large number of anthropological traits and abilities, which are interconnected. Therefore, the aim of this paper is to determine the influence of morphological characteristics as anthropological characteristics of situational-motor, or the accuracy of the basketball game. The survey was conducted in 71 male subjects aged, 15 years ± 6 months, participants school basketball team "Drita" from Gjilani, Kosovo.The sample of variables obtained on the basis of 10 anthropometric measures in the IPB, under which, among other things, three possible estimates of latent anthropometric dimensions of two tests of situational-motor skills and precision. Regression analysis was applied in order to determine the statistical significance of the impact of the entire set of predictive variables on the criterion variable and individual impact of individual predictors on the criterion variable. Analyses were made to the program SPSS 14.0. From the data obtained by regression analysis can be concluded that the better the performance of situational-motor test, or test the accuracy of dribbling in a distance of 5 meters jump shot from the free throw line (MPSŠ) in the patients who had a higher level (AVIS), had longer feet (ADUNA), who had a hand longer (ADURO), greater length of the foot (ADUS), the higher the upper arm (AONL) and larger volume of lower leg (AOPK). The system of prediction of morphological variables has statistically significant effect on the criterion one free throw in the bin (MPSŠ) at 0.000. Morphological analysis of individual predictor variables, we can conclude that a statistically significant effect on the variable with two morphological variables: length of the hand (ADUS) and width of the hand (ASSA).